A secret Christmas wish - McDavid, Cathy, 1956- (McDavid, Cathy, 1956- Wishing Well Springs., 2021)
The magic of Christmas could make her wish come true! A small-town Christmas wedding. What could be more romantic? Unless you're a plus-one for hire like single mom Maia MacKenzie. Too bad handsome cowboy Brent Hayes is her new coworker -- and completely off limits! Neither of them can afford to lose their job... or invest in a relationship. But when she sees Brent's adorable connection with her young son, Maia can't help wishing for a Christmas miracle.